Year of the Rocket (Module II, 2013)
Various Locations. Footage of: Scientists assembling satellite weather balloon.Experimental take-off and landing of the X-13 Vertijet.Jet streaks by over crowds but the wings fall off and the jet explodes. Clip shows the burning wreckage of the jet on the ground.Air Hawk missile launch. Missile strikes plane which then explodes.Rocket launching through a balloon.Sending dog "Laika" into space. "Laika" is put into the chamber with a space helmet on and the rocket is launched and fired. Animation satellite circling earth.Rocket exploding on launch pad.Rocket taking off.